PERILAKU KONSUMTIF GEN Z DALAM PEMBELIAN PRODUK HALAL DI DESA KAPEDI BLUTO SUMENEP - Hayatun; Maksum (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Abstract: The demand for halal products continues to increase along with the growth of the Muslim population in the world, and Indonesia is no exception. High interest in halal products in Kapedi Village, Bluto Sub-District, and Sumenep Regency is also shown by Gen Z. This study aims to analyze the effect of literacy, halal awareness, and religiosity on purchasing decisions for halal-labeled products among Gen Z in Kapedi Village, Bluto. The survey method with a quantitative approach was chosen in this study. Respondents were selected using the purposive sampling method with the criteria of Gen Z who had purchased halal products, with a total of 103 respondents. The results showed that literacy, halal awareness, and religiosity have a positive and significant influence on purchasing decisions for halal-labeled products, both partially and simultaneously. The results of this study have implications that the level of literacy, halal awareness, and religiosity has an important role for Gez Z to improve purchasing decisions for halal products. This finding strengthens the view that the younger generation, despite being exposed to a consumptive culture and global lifestyle, is still influenced by religiosity and awareness of halal factors in choosing halal products. Keywords: Literacy, Halal Awareness, Religiosity, Purchase Decision